Review: therapeutic approaches for circadian modulation of the glioma microenvironment - Nettnin, Ella A.; Nguyen, Thien; Arana, Sophia; Barros Guinle, Maria Isabel; Garcia, Cesar A.; Gibson, Erin M.; Prolo, Laura M. (Frontiers in Oncology, 2023)
High-grade gliomas are malignant brain tumors that are characteristically hard to treat because of their nature; they grow quickly and invasively through the brain tissue and develop chemoradiation resistance in adults. There is also a distinct lack of targeted treatment options in the pediatric population for this tumor type to date. Several approaches to overcome therapeutic resistance have been explored, including targeted therapy to growth pathways (ie. EGFR and VEGF inhibitors), epigenetic modulators, and immunotherapies such as Chimeric Antigen Receptor T-cell and vaccine therapies. One new promising approach relies on the timing of chemotherapy administration based on intrinsic circadian rhythms. Recent work in glioblastoma has demonstrated temporal variations in chemosensitivity and, thus, improved survival based on treatment time of day. This may be due to intrinsic rhythms of the glioma cells, permeability of the blood brain barrier to chemotherapy agents, the tumor immune microenvironment, or another unknown mechanism. We review the literature to discuss chronotherapeutic approaches to high-grade glioma treatment, circadian regulation of the immune system and tumor microenvironment in gliomas. We further discuss how these two areas may be combined to temporally regulate and/or improve the effectiveness of immunotherapies.